The novel centriolar satellite protein SSX2IP targets Cep290 to the ciliary transition zone - Klinger, Maren; Wang, Wen-bo; Kuhns, Stefanie; Bärenz, Felix; Dräger-Meurer, Stefanie; Pereira, Gislene; Gruss, Oliver (Molecular biology of the cell, 2014)
In differentiated human cells, primary cilia fulfill essential functions in converting mechanical or chemical stimuli into intracellular signals. Formation and maintenance of cilia require multiple functions associated with the centriole-derived basal body, from which axonemal microtubules grow and which assembles a gate to maintain the specific ciliary proteome. Here we characterize the function of a novel centriolar satellite protein, synovial sarcoma X breakpoint-interacting protein 2 (SSX2IP), in the assembly of primary cilia. We show that SSX2IP localizes to the basal body of primary cilia in human and murine ciliated cells. Using small interfering RNA knockdown in human cells, we demonstrate the importance of SSX2IP for efficient recruitment of the ciliopathy-associated satellite protein Cep290 to both satellites and the basal body. Cep290 takes a central role in gating proteins to the ciliary compartment. Consistent with that, loss of SSX2IP drastically reduces entry of the BBSome, which functions to target membrane proteins to primary cilia, and interferes with efficient accumulation of the key regulator of ciliary membrane protein targeting, Rab8. Finally, we show that SSX2IP knockdown limits targeting of the ciliary membrane protein and BBSome cargo, somatostatin receptor 3, and significantly reduces axoneme length. Our data establish SSX2IP as a novel targeting factor for ciliary membrane proteins cooperating with Cep290, the BBSome, and Rab8.